DENTIGEROUS CYST IN CHILDREN: A RARE CASE REPORT - Meliawaty, Florence (Journal of Health and Dental Sciences, 2024)
Dentigerous cysts are growths of the jaw's epithelial lining that develop from the dental follicle of unerupted teeth. These cysts are usually found during routine radiography exams, associated with immature teeth. Dentigerous cysts typically don't cause symptoms unless they get big enough to swell. Third, molars and maxillary canines are frequently associated with most dentigerous cysts. A diagnosis is made based on histopathological, radiological, and clinical findings. We describe an instance of a dentigerous cyst that was connected to two immature mandibular premolar teeth. This rare case report discusses the treatment of a dentigerous cyst in the lower premolar region of the left mandible. Under local anesthesia, the patient had surgical treatment that included the removal of two primary teeth and enucleation of the cyst. The evaluation revealed that one week after surgery, the recovery was complete. DOI : 10.54052/jhds.v3n3.p273-280